The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-74152-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anthropogenic habitat fragmentation on the genetic structure and diversity of the malaria vector Anopheles cruzii (Diptera: Culicidae)

Abstract: Fragmentation of natural environments as a result of human interference has been associated with a decrease in species richness and increase in abundance of a few species that have adapted to these environments. The Brazilian Atlantic Forest, which has been undergoing an intense process of fragmentation and deforestation caused by human-made changes to the environment, is an important hotspot for malaria transmission. The main vector of simian and human malaria in this biome is the mosquito Anopheles cruzii. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 99 publications
0
17
1
Order By: Relevance
“…In this study, although more than one mosquito species was observed in the same breeding site, none of the species showed a significant co-occurring behavior with another in the installed traps. Some studies indicate that semiochemicals produced by Culicidae larvae can mediate the oviposition behavior of other species, enabling pregnant females to avoid ovipositing, for example, in breeding sites previously colonized by predators or by interspecific competitors (Navarro-Silva et al 2009). Thus, apparently, eventual semiochemicals produced by the larvae do not seem to mediate the oviposition pattern of the recorded species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, although more than one mosquito species was observed in the same breeding site, none of the species showed a significant co-occurring behavior with another in the installed traps. Some studies indicate that semiochemicals produced by Culicidae larvae can mediate the oviposition behavior of other species, enabling pregnant females to avoid ovipositing, for example, in breeding sites previously colonized by predators or by interspecific competitors (Navarro-Silva et al 2009). Thus, apparently, eventual semiochemicals produced by the larvae do not seem to mediate the oviposition pattern of the recorded species.…”
Section: Discussionmentioning
confidence: 99%
“…The process of hyperfragmentation of the Atlantic Domain landscapes has promoted the phenomenon of taxonomic homogenization of the biota, promoting the proliferation and dominance of groups of animal species with generalist characteristics (Lôbo et al 2011). This forest fragmentation also affects mosquito communities, changing their composition, genetic diversity and behavior (Multini et al 2020;Wilk-da-Silva et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to Multini et al (2020), the genetic structure among the populations of An. (K.) cruzii collected on the ground and in the canopy of trees in the urban environment near the dense Atlantic Forest in São Paulo and the greater genetic diversity in the urban ground-level population indicates an increased insect–human contact [ 78 ].…”
Section: Vector Behavioral and Environmental Changes As Important mentioning
confidence: 99%
“…Anthropogenic modifications of the natural habitat of mosquitoes point to a consequent shift to the anthropophilic behavior of An. (K.) cruzii becoming increasingly common [ 78 , 79 ]. Understanding the impact of human modifications in natural habitats of An.…”
Section: Vector Behavioral and Environmental Changes As Important mentioning
confidence: 99%
“…In addition, increased density of mosquito habitats in human-dominated landscapes can lead to augmented abundance of mosquito vectors, resulting in increased malaria incidence. An interrelated chain of ecological events has been shown to lead to alterations in mosquito species composition in environments that are impacted by habitat loss and fragmentation associated with anthropogenic activities [ 17 , 18 ]. An increased abundance of generalist and opportunistic species [ 19 ], including vectors and infectious pathogens [ 20 ], has been shown to have a potential effect on mosquito communities.…”
Section: Introductionmentioning
confidence: 99%